Effect of consuming ambon banana on increasing hemoglobin levels in pregnant women - Rika Ruspita; Rifa Rahmi; Nurlela (Institute of Computer Science (IOCS), 2022)
The results of the 2018 Basic Health Research stated that in Indonesia 48.9% of pregnant women had anemia. The aim of the study was to determine the effect of consumption of Ambon bananas on increasing Hb levels in pregnant women. This research method uses a quantitative method with the Pre Experiments one group pretest-posttest design. The research sample consisted of 10 respondents using a purposive sampling technique. Based on the univariate results, the highest percentage before administration of Ambon bananas was pregnant women with a hemoglobin level of 9 g/dL in 5 people (50%), a hemoglobin level of 10-11 g/dL in 3 people (30%), a hemoglobin level of 10-11 g/dL dL in 3 persons (30%). level of 8 g/dL in 2 people. people (20%). After giving Ambon bananas to pregnant women who had a hemoglobin level of 12 g/dL in 3 people (30%), a hemoglobin level of 11 g/dL in 5 people (50%), a hemoglobin level of 10 g/dL in 2 people (20%) . Statistical test results obtained P Value 0.004 <0.005 where there was an effect between hemoglobin levels before and after administration of Ambon bananas with a P Value of 0.004 <0.005